HISTOPATHOLOGICAL EVALUATION OF KIDNEYS, LIVER AND SPLEEN OF MICE UNDERGOING REPAIR OF SURGICAL WOUND IN THE ABDOMINAL WALL WITH BOVINE PERICARDIUM PRESERVED WITH GLYCERIN AND GLUTARALDEHYDE - Martins, Caroline Rodrigues Pereira (2011)
ABSTRACT. Martins C.R.P., Silva M.F.A., Nogueira V.A., Prado J.S & Brito M.F. [Histopathological evaluation of kidneys, liver and spleen of mice undergoing repair of surgical wound in the abdominal wall with bovine pericardium preserved with glycerin and glutaraldehyde]. Avaliação anatomopatológica de rins, fígado e baço de camundongos submetidos a implante de pericárdio bovino conservado em glicerina e glutaraldeído em ferida cirúrgica de parede abdominal. Revista Brasileira de Medicina Veterinária, 33(2):103-110, 2011. Curso de Pós-Graduação em Medicina Veterinária, BR-465 km 7, Universidade Federal Rural do Rio de Janeiro, Seropédica, 23890-000, Brasil. E-mail: carolinemedvet@yahoo.com.br The use of bovine pericardium as a biological membrane is widespread in surgical repair because of the low cost, good applicability and it is easily obtained. Glycerin 98% is the chemical agent most used as a biological tissue preservative in veterinary medicine, but studies have shown it is ineffective in eliminating viruses. Glutaraldehyde is a biological tissue preservative. However, the persistence of rabies virus in samples of mice pericardium preserved in 0.625% glutaraldehyde was proven, and probably higher concentrations are required for virucidal action. This study aims to evaluate macro-and microscopically kidney, liver and spleen of 65 mice, 60 of which underwent implantation of bovine pericardium preserved in glycerin 98% and 0.625%, 1% and 1.5% glutaraldehyde, and 5 mice served as controls. The implanted animals were assessed as to their macro and microscopic features of spleen, liver and kidneys. There were no macro or microscopic changes that could be related to the toxicity of these substances.